Familial Multiple Sclerosis with Repetitive Relapses of Manic Psychosis in Two Patients (Mother and Daughter) - Pedro J. Modrego; Jaime Ferrández (Behavioural Neurology)
The clinical presentation of multiple sclerosis (MS) with psychiatric symptoms is uncommon but it is believed that MS patients are twice as likely to be afflicted with bipolar disorder as the general population. We report two cases (mother and daughter) of MS presenting with bipolar disorder in the form of recurrent manic psychosis and whose outcome was favourable with neuroleptics and corticosteroids. In both cases we found multiple hypersignal lesions on brain magnetic resonance imaging (MRI), especially in the right frontal lobe where we observed signs of activity. Apart from clinical and radiological concordance, the patients exhibited similar class I HLA alleles and identical class II HLA alleles. We focused discussion on whether there may be a common genetic susceptibility to both illnesses or whether MS caused psychiatric manifestations. The coincidence of psychiatric and neurological symptoms in most relapses supports the second hypothesis.